Ubiquitous magneto-mechano-electric generator1. Issue 8 (29th August 2015) - Ryu, Jungho; Kang, Ju-Eun; Zhou, Yuan; Choi, Si-Young; Yoon, Woon-Ha; Park, Dong-Soo; Choi, Jong-Jin; Hahn, Byung-Dong; Ahn, Cheol-Woo; Kim, Jong-Woo; Kim, Yang-Do; Priya, Shashank; et al.
<x xml:space="preserve">Abstract</x> A novel energy capturing technique for wasted parasitic magnetic noise based upon a magneto-mechano-electric (MME) generator, consisting of piezoelectric single crystal fibers and Ni metal plate in the form of cantilever structure.